2021
DOI: 10.1002/art.41772
|View full text |Cite
|
Sign up to set email alerts
|

American College of Rheumatology Guidance for the Management of Pediatric Rheumatic Disease During the COVID‐19 Pandemic: Version 2

Abstract: Objective. To provide clinical guidance to rheumatology providers who treat children with pediatric rheumatic disease (PRD) in the context of the coronavirus disease 2019 (COVID-19) pandemic.Methods. The task force, consisting of 7 pediatric rheumatologists, 2 pediatric infectious disease physicians, 1 adult rheumatologist, and 1 pediatric nurse practitioner, was convened on May 21, 2020. Clinical questions and subsequent guidance statements were drafted based on a review of the queries posed by the patients a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 105 publications
0
13
0
Order By: Relevance
“…Despite reassuring data suggesting that children and adolescents with rheumatic disease are not at increased risk of severe outcomes from COVID-19, conventional clinical practice has been for providers to withhold immunosuppressive medications in the context of active infection. Given that symptoms from active COVID-19 can vary widely and there is limited data regarding the impact of immunosuppressive medications on those symptoms, clinical guidance provided by the American College of Rheumatology (ACR) recommends that disease-modifying antirheumatic drugs be held in cases of con rmed symptomatic COVID-19 (14). It is suggested that medications may be restarted 7-14 days after resolution of fever and respiratory symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Despite reassuring data suggesting that children and adolescents with rheumatic disease are not at increased risk of severe outcomes from COVID-19, conventional clinical practice has been for providers to withhold immunosuppressive medications in the context of active infection. Given that symptoms from active COVID-19 can vary widely and there is limited data regarding the impact of immunosuppressive medications on those symptoms, clinical guidance provided by the American College of Rheumatology (ACR) recommends that disease-modifying antirheumatic drugs be held in cases of con rmed symptomatic COVID-19 (14). It is suggested that medications may be restarted 7-14 days after resolution of fever and respiratory symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…15 According to the American College of Rheumatology Guidance, the task force unanimously agreed that primary control of underlying rheumatic disease with judicious use of immunosuppressive treatment is of utmost importance, to minimize diseases flares and immune dysregulation. 16 In a cohort of children with rheumatic diseases, biological treatments did not have a negative impact on COVID-19 outcome and the authors recommended that caution should be taken during the infection period because interruption of treatment might exacerbate the rheumatic disease activity. The decision should be taken on individual basis considering the current biological agent, primary disease status, COVID-19 severity, and the available guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…The ACR created a COVID-19 Clinical Guidance Task Force to develop and disseminate recommendations on vaccination, treatment for acute infection, and guidance on management of immunosuppressive medications in patients infected with COVID-19. [26][27][28] High-quality data regarding the impact of COVID-19 in rheumatic disease populations were lacking early in the pandemic, creating a vacuum that was often filled with poorly designed studies and resulting misinformation, such as the proposed utility of hydroxychloroquine in the treatment of acute viral infection. Colleagues in the rheumatology community, such as the GRA, offered a helpful counter to claims made in the media and represented a rational voice calling for a cautious, and scientific, approach to investigations regarding COVIDrelated therapies.…”
Section: Impact On Clinical Trainingmentioning
confidence: 99%